Effects of processing methods on the nutritional value of sorghum for weaned pigs - Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred twenty-six weaned, crossbred pigs averaging 14 kg (31 lbs.) initially were used to evaluate the effects of various methods of processing sorghum grain. Processing methods evaluated were: pelleting, extruding, micronizing, high-moisture grain stored in an oxygen limiting structure, and high-moisture grain treated with propionic acid. Except for pelleting, only the grain (sorghum) was exposed to the various processing methods. After being processed, the sorghum was ground and incorporated into a 18% sorghum-soybean meal diet. None of the processing methods increased weight gain of weaned pigs over that by pigs fed the control diet (ground sorghum fed as a meal). Extruding reduced weight gain. Pelleting was the only processing method that improved feed efficiency.
Swine Day '76 is known as Swine Day, 1976
Keywords: Swine; Nutrition; Sorghum; Weanling pigs; Feed efficiency; Propionic acid